2009
DOI: 10.1007/s00441-009-0797-7
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine sulphate does not increase extracellular matrix production at low oxygen tension

Abstract: Low oxygen tension may change the dependence of chondrocytes on exogenous carbohydrate sources. In this study, we have investigated whether glucosamine sulphate (GS) stimulates proteoglycan synthesis, the mRNA expression of aggrecan and of type II collagen, and UDP-sugar levels in bovine primary chondrocytes under a low oxygen (O(2)) atmosphere. Chondrocytes from bovine femoral condyles were cultivated with or without GS or sulphate at various concentrations in low- (5.5 mM) or high-glucose (25 mM) DMEM under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Our previous study has shown that 5% O 2 significantly increases GAG synthesis and the expression of aggrecan and procollagen α 1 (II) mRNA when bovine primary chondrocytes are cultured in monolayers (Qu et al 2009). Thus, our hypothesis has been that a positive effect would be obtained when normal mature chondrocytes are cultured under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our previous study has shown that 5% O 2 significantly increases GAG synthesis and the expression of aggrecan and procollagen α 1 (II) mRNA when bovine primary chondrocytes are cultured in monolayers (Qu et al 2009). Thus, our hypothesis has been that a positive effect would be obtained when normal mature chondrocytes are cultured under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 98%
“…The quantitative real-time RT-PCR analyses of these genes were performed by using the Mx3000P Real-Time PCR System (Stratagene, La Jolla, Calif., USA; Qu et al 2007). The primer sequences of GAPDH (Qu et al 2009), aggrecan (Bosnakovski et al 2006), procollagen α 1 (II) (Galois et al 2006), procollagen α 2 (I) (Galois et al 2006) and HAS2 (Schoenfelder and Einspanier 2003) used for quantitative RT-PCR in this study are available in the cited references.…”
Section: Pg Separation With Agarose Gel Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…Renilla luciferase activity was used to normalize the transfection efficiency. The transfection efficiency was previously shown to be 27 % (Qu et al 2009). The experiment was repeated three times.…”
Section: Taurine Transporter Promoter Activity In Hypoand Hypertonic mentioning
confidence: 95%
“…Dual-luciferase ® reporter gene assay (Promega, Madison, WI, USA) was performed as previously described (Qu et al 2009), using taurine transporter firefly luciferase reporter plasmid, which contains −124 to +46 region of rat taurine transporter promoter (Han et al 2000;Ito et al 2004), and Renilla luciferase plasmid at 10:1 ratio. We also used a taurine transporter reporter plasmid, which has a mutated tonicity-responsive element (TonE) (Ito et al 2004) to verify that the induction of the reporter gene by hypertonicity was being regulated by this region.…”
Section: Taurine Transporter Promoter Activity In Hypoand Hypertonic mentioning
confidence: 99%